An inquiry into the causes and nature of organization : some observations on the international working men's association, 1864-1872/1876 - Devreese, D.E. (Leiden : E.J. Brill, 1988)
Bibliotheek François Vercammen
Overdruk van Internationalism in the Labour movement 1830-1940
Engels
Brochure
Keywords: arbeidersbeweging